AKTIVASI KBBI VI DARING DALAM KAJIAN HERMENEUTIKA SCHLEIERMACHER PADA LAGU MENDARAH KARYA NADIN AMIZAH - Gulyanto, Bambang; Maulidiah, Rina Hayati; Siregar, Evi Supriyani; Daulay, Alwi Syahputra (Smart Education, 2025)
Abstract: This research aims to analyze the meaning of words by utilizing KBBI VI and language style in the lyrics of the song